Letter from Herman Mark to Max Bredig, December 1, 1938 - Mark, H. F. (Herman Francis) (1938)
Herman Francis Mark (1895-1992) was an Austrian chemist known for his contributions to polymer science, X-ray diffraction, and his work at IG Farben. In 1938 Mark started preparing to leave Austria. He was unable to make it out of the country before Hitler invaded Austria and was sent to a Gestapo prison. After his release, he was able to immigrate to America by first entering Canada. He continued his research in polymers in Brooklyn, New york.
Keywords: Mark, H. F. (Herman Francis), 1895-1992; Bredig, Max Albert, 1902-1977; Chemists